A 6ps Resolution Pulse Shrinking Time-to-Digital Converter as Phase Detector in Multi-Mode Transceiver - Liu, Yue; Vollenbruch, Ulrich; Chen, Yangjian; Wicpalek, Christian; Maurer, Linus; Mayer, Thomas; Boos, Zdravko; Weigel, Robert (IEEE Radio and Wireless Symposium, 2008)
This paper presents a new phase detector in an all digital phase locked loop which converts the phase difference between one reference clock edge and one divided oscillator edge into a digital word. This digital word can be converted into a digital representation of the actual phase error which can be utilized in an all digital phase locked loop. 6 ps resolution for this time-to-digital converter (TDC) is realized in a standard 0.13 mum CMOS technology. Its full- scale-range (FSR) is 4500 ps.
elib2cris::1512001600,yue2008
Keywords: convertors; digital phase locked loops; oscillators; phase detectors; transceivers; CMOS technology; digital phase locked loop; multimode transceiver; oscillator edge; phase detector; pulse shrinking time-to-digital converter; size 0.13 mum; CMOS technology; Clocks; Gas detectors; Phase detection; Phase locked loops; Phase noise; Power generation; Radio frequency; Space technology; Transceivers; PLL; TDC; all digital PLL